Integrating serum pharmacochemistry and network pharmacology to explore potential compounds and mechanisms of Alpiniae oxyphyllae fructus in the treatment of cellular senescence in diabetic kidney disease - Yan, Zijie; Zhang, Lin; Kang, Yu; Liu, Shuman; Li, Xiaoyan; Li, Lidan; Rui, Kai; Xiao, Man; Xie, Yiqiang (Frontiers in Medicine, 2024)
Background: Diabetic kidney disease (DKD), one of the microvascular complications in patients with diabetes mellitus, is a common cause of end-stage renal disease. Cellular senescence is believed to be an essential participant in the pathogenesis of DKD. Although there is evidence that Alpiniae oxyphyllae fructus (AOF) can ameliorate DKD progression and organismal senescence, its ability to ameliorate renal cellular senescence in DKD as well as active components and molecular mechanisms remain to be explored. Purpose: This study aimed to investigate the role of AOF in the treatment of cellular senescence in DKD and to explore its active components and potential molecular mechanisms. Methods: The pharmacological efficacy of AOF in ameliorating cellular senescence in DKD was assessed by establishing DKD mouse models and HK-2 cells under high glucose stress. UHPLC-QTOF-MS was used to screen the active compounds in AOF, which were used in conjunction with network pharmacology to predict the molecular mechanism of AOF in the treatment of cellular senescence in DKD. Results: In vivo experiments showed that AOF reduced GLU, mAlb, Scr, BUN, MDA, SOD levels, and ameliorated renal pathological damage and renal cell senescence in DKD mice. In vitro experiments showed that AOF-containing serum improved the decline in HK-2 cell viability and alleviated cellular senescence under high glucose intervention. The results of the UHPLC-QTOF-MS screened 26 active compounds of AOF. The network pharmacological analyses revealed that Cubebin, 2',6'-dihydroxy-4'-methoxydihydrochalcone, Chalcone base + 3O,1Prenyl, Batatasin IV, Lucidenolactone were the five core compounds and TP53, SRC, STAT3, PIK3CA, AKT1 are the five core targets of AOF in the treatment of DKD. Molecular docking simulation results showed that the five core compounds had good binding ability to the five core targets. Western blot validated the network pharmacological prediction results and showed that AOF and AOF-containing serum down-regulate the expression of TP53, and phosphorylation of SRC, STAT3, PIK3CA, AKT. Conclusion: Our study shows that AOF may delay the development of cellular senescence in DKD by down-regulating the levels of TP53, and phosphorylation of SRC, STAT3, PIK3CA, AKT.